Ion exchange membrane as well as preparation method and application thereof
By using stacked nano-scale pore layers and sub-nano-scale pore layers as support bodies in the ion exchange membrane, the swelling of the ion exchange polymer and the promotion of ion dehydration are limited, and the problem of great influence of water transmembrane migration in the prior art is solved, and an efficient electrodialysis concentration effect is achieved.
Patent Information
- Application Number
- CN202510029566.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-01
AI Technical Summary
The existing ion exchange membrane has a great impact on the transmembrane migration of water under high salt difference operating conditions, making it difficult to achieve high concentration, and the swelling of ion exchange polymers is difficult to suppress in the micron-scale space, resulting in serious penetration of water concentration difference.
The nano-scale pore layer and sub-nano-scale pore layer arranged in stacks are used as support bodies. The ion exchange polymer swells in the nano-space of the nano-scale pore layer are limited, while the sub-nano-scale pore layer ensures sufficient dehydration of ions, thereby reducing the permeability and electromigration of water.
A high-rate concentration of 155.21 g/L of single-stage NaCl salt difference was achieved, and the salt-water selectivity did not show significant attenuation during 72 hours of continuous operation, and the process was safe, simple and low energy consumption.
Smart Images

Figure CN119733575A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of membrane separation technology, and in particular to an ion exchange membrane and a preparation method and application thereof. Background Art
[0002] The sewage treatment industry is an important foundation for clean production in modern society and healthy water for human life. Membrane concentration technology is an important support for achieving high quality and low consumption in sewage resource utilization and near-zero discharge treatment of wastewater. The membrane concentration technologies currently used in industrial applications mainly include: ultrafiltration, microfiltration, nanofiltration, reverse osmosis, forward osmosis and electrodialysis. Multi-membrane coupling and multi-stage operation are currently the main strategies for increasing the concentration of concentrated liquid (reduction of high brine). During this period, problems such as lengthy process routes, cumbersome operation control, and high investment costs are inevitable. Therefore, there is an urgent need to develop new membranes or new membrane concentration technologies with outstanding single-stage concentration capabilities.
[0003] Electrodialysis technology achieves water desalination and salt concentration by driving the directional migration of ions in anion / cation exchange membrane stacks through electric fields. It has been promoted in engineering applications due to its advantages such as simple operation, considerable energy consumption, and controllable water quality. Its core component is the anion / cation exchange membrane with positive / negative charge. The selectivity of the membrane for ions with different charges is the main process of electrodialysis. However, facing the demand for high concentration, the influence of water migration across the membrane under high salinity difference operating conditions is particularly prominent. Therefore, the ion exchange membrane with high ion permeability and low water permeability (i.e., having) is the key to achieving high concentration by electrodialysis technology.
[0004] The migration mechanism of water in ion exchange membranes is mainly concentration-driven permeation and electroosmosis in which ions migrate across the membrane and drag water molecules in the surrounding hydration layer across the membrane. The migration channel of water is the channel formed between the ion exchange polymer chains by the water clusters around the hydrophilic groups, as well as the interface space between the ion exchange polymer and the support. In order to reduce the migration of water in the membrane, studies have shown that regulating the open area of the support (at the micrometer scale) and the surface charge of the support have an effect on the permeability of the ion exchange membrane. However, the swelling of ion exchange polymers cannot be effectively suppressed in the micrometer-scale space, resulting in the swelling and expansion of the water transfer channel between the polymer chains, and the serious water concentration permeation. In addition, studies have found that the use of porous materials with sub-nanometer pore characteristics (such as metal organic frameworks, two-dimensional layered transition metal nanosheets, graphene, etc.) as ion exchange membrane additives can cause dehydration of ions across the membrane, which may reduce the electroosmosis of water. However, ion exchange membranes that synergistically reduce water migration by limiting the swelling of ion exchange polymers and promoting ion dehydration have not yet been studied.
[0005] Based on this, it is necessary to provide an ion exchange membrane and its preparation method that can inhibit the expansion of interchain water transfer channels caused by swelling of ion exchange polymers and have good dehydration effect, so that it can be applied to electrodialysis technology to achieve short-process and high-rate concentration of saline wastewater. Summary of the invention
[0006] In view of this, one object of the present application is to provide an ion exchange membrane, which is supported by a stacked nanoscale pore layer and a sub-nanoscale pore layer. The ion exchange polymer can be limited in swelling in the nanospace of the nanoscale pore layer to achieve reduced water permeability, while the sub-nanoscale pore layer can ensure sufficient dehydration of ions.
[0007] Another object of the present application is to provide a method for preparing an ion exchange membrane.
[0008] Yet another object of the present application relates to the use of ion exchange membranes.
[0009] Another object of the present application is to provide an electrodialysis device.
[0010] To achieve the above-mentioned objectives, the first aspect of the present application proposes an ion exchange membrane, comprising a support body, wherein the support body comprises a stacked nanoscale pore layer and a sub-nanoscale pore layer, at least a portion of the surface of the nanoscale pore layer facing away from the sub-nanoscale pore layer is provided with at least a first coating, at least a portion of the surface of the sub-nanoscale pore layer facing away from the nanoscale pore layer is provided with at least a second coating, the materials of the first coating and the second coating both comprise ion exchange polymers, and the material of the first coating is embedded in at least a portion of the nanoscale pores of the nanoscale pore layer.
[0011] In some embodiments, the sub-nanoscale pores in the sub-nanoscale porous layer have a pore size range of 0.2-0.9 nm.
[0012] In some embodiments, the sub-nanoscale pore layer has a thickness of 10-500 nm.
[0013] In some embodiments, the diameter of the nanoscale pores in the nanoscale porous layer ranges from 5 to 800 nm.
[0014] In some embodiments, the thickness of the nanoscale pore layer is 10-200 μm.
[0015] In some embodiments, the sub-nanoscale pore layer is a sub-nanopore film formed of a polymer, and the polymer includes at least one of polyamide, polyester, and polyphenol.
[0016] In some embodiments, the nanoscale pore layer is a porous structure membrane constructed of organic materials or inorganic materials; the organic material includes at least one of polysulfone, polyethylene, polyvinylidene fluoride, and polyacrylonitrile; and / or the inorganic material includes at least one of molecular sieves, porous ceramics, titanium oxide, and silicon oxide.
[0017] In some embodiments, the ion exchange polymer includes at least one of a sulfonic acid group-modified molecular chain polymer having a negative charge and a quaternary ammonium group-modified molecular chain polymer having a positive charge, preferably at least one of Nafion, Aquivion, Fumiom, and PiperION.
[0018] In some embodiments, the ion exchange polymer loading in the ion exchange membrane is 2-200 mg / cm 2 .
[0019] In some embodiments, the first coating layer and the second coating layer are made of the same material.
[0020] In some embodiments, the first coating has a thickness of 2-200 μm.
[0021] In some embodiments, the second coating layer has a thickness of 0.1-10 μm.
[0022] The second aspect of the present application provides a method for preparing an ion exchange membrane, comprising the steps of forming the first coating on the nanoscale pore layer and forming the second coating on the sub-nanoscale pore layer;
[0023] The forming of the first coating on the nanoscale pore layer comprises: coating the dispersion of the ion exchange polymer on at least a portion of the surface of the nanoscale pore layer on a side away from the sub-nanoscale pore layer, and then performing a first drying;
[0024] The forming of the second coating layer on the sub-nanoscale pore layer comprises: coating the dispersion of the ion exchange polymer on at least a portion of the surface of the sub-nanoscale pore layer facing away from the nanoscale pore layer, and then performing a second drying.
[0025] In some embodiments, the step of forming the first coating layer on the nanoscale pore layer is performed first, and then the step of forming the second coating layer on the sub-nanoscale pore layer is performed.
[0026] In some embodiments, the method for preparing the ion exchange membrane further includes: cyclically performing the step of forming the first coating on the nanoscale pore layer and the step of forming the second coating on the sub-nanoscale pore layer until the ion exchange polymer reaches the expected loading amount to obtain the ion exchange membrane.
[0027] In some embodiments, the method for preparing the ion exchange membrane further includes: mixing the ion exchange polymer with an organic solvent to obtain a dispersion of the ion exchange polymer.
[0028] In some embodiments, the expected loading amount is the ratio of the loading mass of the ion exchange polymer after drying to the support area, and the expected loading amount is 2-200 mg / cm 2 .
[0029] In some embodiments, the organic solvent includes at least one of ethanol, N-methylpyrrolidone, and dimethylformamide.
[0030] In some embodiments, the mass fraction of the ion exchange polymer in the ion exchange polymer dispersion is 0.1-50%.
[0031] In some embodiments, the method for preparing the ion exchange membrane further comprises: after the ion exchange polymer reaches a desired loading amount, performing a third drying on the ion exchange membrane.
[0032] In some embodiments, the third drying temperature is 30-100°C.
[0033] In some embodiments, the third drying time is 1-48 hours.
[0034] In some embodiments, the third drying method includes at least one of air drying, vacuum drying, and constant temperature heating.
[0035] In some embodiments, the coating methods in the step of forming the first coating on the nanoscale pore layer and the step of forming the second coating on the sub-nanoscale pore layer both include at least one of spray coating, scraper coating, and spin coating.
[0036] In some embodiments, in the step of forming the first coating layer on the nanoscale porous layer, the surface of the nanoscale porous layer facing away from the sub-nanoscale porous layer is the upper surface of the support.
[0037] In some embodiments, in the step of forming the second coating layer on the sub-nanoscale pore layer, the surface of the sub-nanoscale pore layer facing away from the nanoscale pore layer is the upper surface of the support.
[0038] In some embodiments, the first drying and the second drying methods both include at least one of forced air drying, vacuum drying, and constant temperature heating.
[0039] In some embodiments, the first drying and the second drying are performed at a temperature of 30-100°C.
[0040] In some embodiments, the first drying and the second drying are both performed for 0.1-2 hours.
[0041] The third aspect of the present application relates to the application of the ion exchange membrane described in the present application or the ion exchange membrane prepared by the method for preparing the ion exchange membrane described in the present application in the field of membrane separation technology.
[0042] The fourth aspect of the present application proposes an electrodialysis device, comprising an anode, a cathode, a cation exchange membrane and an anion exchange membrane, wherein the cation exchange membrane and / or the anion exchange membrane is the ion exchange membrane described in the present application or an ion exchange membrane prepared by the preparation method of the ion exchange membrane described in the present application.
[0043] The ion exchange membrane described in this application can at least bring the following beneficial effects:
[0044] 1. The nano-support part (i.e., nano-scale pore layer) in the membrane is the main storage space for ion exchange polymers. The swelling behavior of ion exchange polymers is limited in the nano-confined space. The lack of free swelling space between polymers leads to the obstruction of water permeation migration channels, which reduces the permeability of the membrane. The sub-nanometer support thin layer (i.e., sub-nanometer pore layer) in the membrane dehydrates the passing ions due to the size effect, thereby reducing the electrical permeability of water. The low permeability and dehydration of the nano-sub-nanometer co-supported ion exchange membrane jointly achieve its superior salt-water selectivity.
[0045] 2. The nano-subnano co-supported ion exchange membrane of the present application was applied to membrane concentration of electrodialysis technology, achieving a single-stage NaCl salt difference of 155.21 g / L (fresh water: 16.31 g / L; concentrated water: 171.52 g / L), and the salt-water selectivity showed no obvious attenuation during 72 hours of continuous operation.
[0046] 3. Different nano-subnanostructure supports can be selected and assembled with ion exchange polymers to form ion exchange membranes. This type of ion exchange membrane has extremely high salt-water selectivity and will have broad prospects in the field of membrane concentration.
[0047] The method for preparing the ion exchange membrane described in the present application, in addition to the beneficial effects of the ion exchange membrane described in the present application, can also bring the following beneficial effects:
[0048] The process is safe, simple, low energy and scalable.
[0049] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.
[0051] in:
[0052] Figure 1 This is a schematic diagram of the process of forming a first coating layer and a second coating layer in a method for preparing an ion exchange membrane according to an exemplary embodiment of the present application.
[0053] Figure 2 This is a transmission electron microscope (TEM) image of the support in Example 1.
[0054] Figure 3 This is a transmission electron microscope (TEM) image of the ion exchange membrane prepared in Example 1.
[0055] Figure 4 Schematic diagram of the electrodialysis salt concentration test device.
[0056] Figure 5 This is the effluent concentration diagram of the electrodialysis salt concentration test in Application Example 1.
[0057] Figure 6 This is the maximum concentration difference diagram of the electrodialysis salt concentration test in Application Example 2.
[0058] Figure 7 The effluent salinity and concentrate quality changes of the ion exchange membrane prepared in Examples 1 and 2 in Application Example 3 in the electrodialysis NaCl concentration test.
[0059] Reference numerals:
[0060] 1- anode; 2- second position; 3- third position; 4- fourth position; 5- fifth position; 6- cathode; 7- electrode liquid; 8- concentrated liquid; 9- desalinated liquid. DETAILED DESCRIPTION
[0061] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0062] In this application, the disclosure of numerical ranges includes all values within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.
[0063] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.
[0064] The term "and / or", when used in a list of two or more items, means that any of the listed items can be used alone or in combination with any one or more of the listed items. For example, the expression "A and / or B" is intended to mean A or B or A and B, that is, only A, only B, or a combination of A and B.
[0065] <Ion Exchange Membrane>
[0066] The ion exchange membrane of the embodiment of the present application includes a support body, which includes a nanoscale pore layer and a sub-nanoscale pore layer arranged in a stacked manner, at least a first coating is provided on at least a portion of the surface of the nanoscale pore layer facing away from the sub-nanoscale pore layer, and at least a second coating is provided on at least a portion of the surface of the sub-nanoscale pore layer facing away from the nanoscale pores, the materials of the first coating and the second coating both include ion exchange polymers, and the material of the first coating is embedded in at least a portion of the nanoscale pores of the nanoscale pore layer.
[0067] It is understandable that when the first coating and the second coating are formed on the surface of the nanoscale pore layer and the sub-nanoscale pore layer by coating (for example, spraying, etc.), the dispersion of the ion exchange polymer used for coating is not only formed on the surface of the nanoscale pore layer and the sub-nanoscale pore layer, but also enters the nanoscale pores of the nanoscale pore layer due to the larger pore size of the nanoscale pores of the nanoscale pore layer, so that the material of the final first coating is embedded in at least a portion of the nanoscale pores. However, due to the smaller pore size of the sub-nanoscale pores of the sub-nanoscale pore layer, the dispersion of the ion exchange polymer used for coating cannot enter the pore size of the sub-nanoscale pores of the sub-nanoscale pore layer. Therefore, the material of the second coating only exists on at least a portion of the surface of the sub-nanoscale pore layer away from the nanoscale pores. In addition, if there is a large amount of dispersion of ion exchange polymer entering the nanoscale pores of the nanoscale pore layer, in some cases, it may contact the surface of the sub-nanoscale pore layer adjacent to the nanoscale pore layer, so that the material of the final first coating layer contacts the surface of the sub-nanoscale pore layer adjacent to the nanoscale pore layer; in other cases, it may also fill the entire nanoscale pores and contact the surface of the sub-nanoscale pore layer adjacent to the nanoscale pore layer. Therefore, in some cases, the material of the first coating is embedded in at least part of the nanoscale pores of the nanoscale pore layer and contacts the surface of the sub-nanoscale pore layer adjacent to the nanoscale pore layer. In other cases, the material of the first coating is embedded in at least part of the nanoscale pores of the nanoscale pore layer and contacts the surface of the nanoscale pore layer adjacent to the sub-nanoscale pore layer.
[0068] As an optional example, the entire surface of the nanoscale pore layer facing away from the sub-nanoscale pore layer is provided with at least one first coating layer, and the entire surface of the sub-nanoscale pore layer facing away from the nanoscale pore layer is provided with at least one second coating layer.
[0069] As an optional example, the diameter of the sub-nanoscale pores in the sub-nanoscale pore layer is in the range of 0.2-0.9 nm, and may further be 0.3-0.8 nm, 0.2-0.6 nm, 0.2-0.5 nm or 0.4-0.7 nm, etc.
[0070] In the embodiments of the present application, the pore size range of the sub-nanoscale pores in the sub-nanoscale pore layer is 0.2-0.9nm, which can take into account both membrane resistance and dehydration performance, so that the ion exchange membrane has a smaller membrane resistance and better dehydration performance; if it is lower than 0.2nm, the membrane resistance is too high; if it is higher than 0.9nm, the dehydration performance decreases.
[0071] As a preferred example, the diameter of the sub-nanoscale pores in the sub-nanoscale porous layer is 0.45 nm.
[0072] In some embodiments, the thickness of the sub-nanoscale pore layer is 10-500 nm, including but not limited to 15 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm or 480 nm.
[0073] In some embodiments, the pore size of the nanoscale pores in the nanoscale porous layer ranges from 5 to 800 nm, and may further range from 50 to 700 nm, 100 to 600 nm, 200 to 500 nm, 300 to 400 nm, 5 to 200 nm, 5 to 400 nm or 100 to 500 nm.
[0074] In some embodiments, the thickness of the nanoscale pore layer is 10-200 μm, including but not limited to 20 μm, 50 μm, 100 μm, 150 μm or 190 μm.
[0075] In some embodiments, the sub-nanoscale pore layer is a sub-nanopore film formed of a polymer.
[0076] Exemplarily, in the sub-nanoscale pore layer, the polymer includes but is not limited to at least one of polyamide, polyester, polyphenol, etc. Among them, polyamide includes but is not limited to at least one of polyamide-6, polyamide-66 and polyamide-610, etc., polyester includes but is not limited to at least one of polyethylene terephthalate, polybutylene terephthalate, etc., and polyphenol includes but is not limited to at least one of polyphenolamine and plant polyphenol, etc.
[0077] In some embodiments, the nanoscale pore layer is a porous structure membrane constructed of organic or inorganic materials.
[0078] Exemplarily, the organic material includes but is not limited to at least one of polysulfone, polyethylene, polyvinylidene fluoride, polyacrylonitrile and the like.
[0079] Exemplarily, the inorganic material includes but is not limited to at least one of molecular sieves, porous ceramics, titanium oxides, silicon oxides, etc. Among them, molecular sieves include but are not limited to at least one of 3A (potassium A type) molecular sieves, 4A (sodium A type) molecular sieves, 5A (calcium A type) molecular sieves, 10Z (calcium Z type) molecular sieves, etc., porous ceramics include but are not limited to at least one of foam ceramics (for example, zirconia ceramic sheets, etc.), honeycomb ceramics, etc., titanium oxides include at least one of titanium dioxide, TiO, etc., and silicon oxides include at least one of silicon dioxide, silicon monoxide, etc.
[0080] In some embodiments, the nanoscale pore layer and the sub-nanoscale pore layer are laminated and fixed together by heat pressing, ultrasonic welding, or the like.
[0081] It should be noted that in the examples of the present application, the support can be a commercially available product or can be homemade. When homemade, the support is prepared by, for example, phase inversion and interfacial polymerization.
[0082] In some embodiments, the ion exchange polymer includes at least one of a molecular chain polymer modified with a sulfonic acid group and having a negative charge, and a molecular chain polymer modified with a quaternary ammonium group and having a positive charge.
[0083] Exemplarily, the negatively charged molecular chain polymer modified with sulfonic acid groups includes, but is not limited to, at least one of Nafion (also known as perfluorosulfonic acid resin) and Aquivion.
[0084] Exemplarily, the molecular chain polymer having positive charge after modification with quaternary ammonium groups includes but is not limited to at least one of Fumiom, PiperION and the like.
[0085] As an optional example, the ion exchange polymer is at least one of Nafion, Aquivion, Fumiom, and PiperION.
[0086] In some embodiments, the ion exchange polymer loading in the ion exchange membrane is 2-200 mg / cm 2 , including but not limited to 5mg / cm 2 、30mg / cm 2 、50mg / cm 2 、75mg / cm 2 、100mg / cm 2 、125mg / cm 2 、150mg / cm 2 、175mg / cm 2 or 200mg / cm 2 wait.
[0087] In the embodiments of the present application, the loading amount of the ion exchange polymer refers to the ratio between the loading mass of the ion exchange polymer (including the ion exchange polymer in the first coating on the nanoscale pore layer side and the ion exchange polymer in the second coating on the sub-nanoscale pore layer side) in the entire ion exchange membrane and the support area on one side of the support body (the support area on the nanoscale pore layer side or the support area on the sub-nanoscale pore layer side), which is essentially the same as the expected loading amount described later.
[0088] In some embodiments, the first coating layer and the second coating layer are made of the same material. In this case, depending on the material, the ion exchange membrane of the embodiment of the present application can be used as an anion exchange membrane or a cation exchange membrane.
[0089] In the embodiments of the present application, even if the amount of material used is the same, due to the differences in pore size and structure between the nanoscale pore layer and the sub-nanoscale pore layer, as described above, the material of the first coating will enter at least part of the nanoscale pores of the nanoscale pore layer during the coating process to form the coating, while the material of the second coating will not enter the sub-nanoscale pores of the sub-nanoscale pore layer during the coating process to form the coating, resulting in differences in thickness and morphology between the final first coating and the second coating.
[0090] In some embodiments, the thickness of the first coating layer is 2-200 μm, including but not limited to 10 μm, 50 μm, 100 μm, 150 μm or 180 μm, etc.
[0091] In some embodiments, the thickness of the first coating layer is 0.1-10 μm, including but not limited to 1 μm, 3 μm, 5 μm, 7 μm or 9 μm.
[0092] The ion exchange membrane of the embodiment of the present application can at least bring the following beneficial effects:
[0093] 1. The nano-support part (i.e., nano-scale pore layer) in the membrane is the main storage space for ion exchange polymers. The swelling behavior of ion exchange polymers is limited in the nano-confined space. The lack of free swelling space between polymers leads to the obstruction of water permeation migration channels, which reduces the permeability of the membrane. The sub-nanometer support thin layer (i.e., sub-nanometer pore layer) in the membrane dehydrates the passing ions due to the size effect, resulting in a decrease in water electro-osmosis, which leads to a decrease in the electro-migration number of the membrane. The low permeability and dehydration of the nano-sub-nanometer co-supported ion exchange membrane jointly achieve its superior salt-water selectivity.
[0094] 2. The nano-subnano co-supported ion exchange membrane of the present application was applied to membrane concentration of electrodialysis technology, achieving a single-stage NaCl salt difference of 155.21 g / L (fresh water: 16.31 g / L; concentrated water: 171.52 g / L), and the salt-water selectivity showed no obvious attenuation during 72 hours of continuous operation.
[0095] 3. Different nano-subnanostructure supports can be selected and assembled with ion exchange polymers to form ion exchange membranes. This type of ion exchange membrane has extremely high salt-water selectivity and will have broad prospects in the field of membrane concentration.
[0096] <Method for preparing ion exchange membrane>
[0097] The method for preparing the ion exchange membrane of the embodiment of the present application can be used to prepare the ion exchange membrane of the embodiment of the present application.
[0098] The method for preparing the ion exchange membrane of the embodiment of the present application comprises the steps of forming the first coating on the nanoscale pore layer and forming the second coating on the sub-nanoscale pore layer; wherein:
[0099] The forming of the first coating on the nanoscale pore layer comprises: coating the dispersion of the ion exchange polymer on at least a portion of the surface of the nanoscale pore layer on a side away from the sub-nanoscale pore layer, and then performing a first drying;
[0100] The forming of the second coating layer on the sub-nanoscale pore layer comprises: coating the dispersion of the ion exchange polymer on at least a portion of the surface of the sub-nanoscale pore layer facing away from the nanoscale pore layer, and then performing a second drying.
[0101] In some embodiments, the first drying and the second drying both include at least one of air drying, vacuum drying, and constant temperature heating, preferably air drying.
[0102] Exemplarily, forced air drying is performed in a laboratory forced air oven, vacuum drying is performed in a vacuum drying oven, and constant temperature heating is performed on a constant temperature heating table.
[0103] In some embodiments, the first drying and the second drying temperatures are both 30-100° C., including but not limited to 35° C., 50° C., 60° C., 70° C., 80° C., or 90° C. The first drying and the second drying temperatures within the above range can promote the volatilization of the organic solvent in the dispersion of the ion exchange polymer.
[0104] In some embodiments, the first drying time and the second drying time are both 0.1-2 hours, including but not limited to 0.5 hours, 1 hour or 1.5 hours.
[0105] It should be noted that, in the embodiments of the present application, the first drying and the second drying are both intended to dry the organic solvent on the surface of the coating layer formed by coating.
[0106] It should also be noted that in the embodiments of the present application, the order in which the first coating and the second coating are formed may not be limited, such as: first forming the first coating and then forming the second coating; or, first forming the second coating and then forming the first coating; or, forming the first coating and the second coating at the same time.
[0107] As a preferred example, the step of forming the first coating layer on the nanoscale pore layer is performed first, and then the step of forming the second coating layer on the sub-nanoscale pore layer is performed.
[0108] In some embodiments, the method for preparing the ion exchange membrane further includes: cyclically performing the step of forming the first coating on the nanoscale pore layer and the step of forming the second coating on the sub-nanoscale pore layer until the ion exchange polymer reaches the expected loading amount to obtain the ion exchange membrane.
[0109] In some embodiments, the method for preparing the ion exchange membrane further includes: mixing the ion exchange polymer with an organic solvent to obtain a dispersion of the ion exchange polymer.
[0110] In some embodiments, the expected loading amount is the ratio of the loading mass of the ion exchange polymer after drying to the support area, and the expected loading amount is 2-200 mg / cm 2 , including but not limited to 5mg / cm 2 、30mg / cm 2 、50mg / cm 2 、75mg / cm 2 、100mg / cm 2 、125mg / cm 2 、150mg / cm 2 、175mg / cm 2 or 200mg / cm 2 wait.
[0111] In some embodiments, the organic solvent includes but is not limited to at least one of ethanol, N-methylpyrrolidone, dimethylformamide, and the like.
[0112] In some embodiments, the mass fraction of the ion exchange polymer in the dispersion of the ion exchange polymer is about 0.1-50%, including but not limited to 0.1%, 1%, 10%, 20%, 30%, 40% or 50%, etc.
[0113] In some embodiments, the method for preparing the ion exchange membrane further comprises: after the ion exchange polymer reaches a desired loading amount, performing a third drying on the ion exchange membrane.
[0114] In the embodiments of the present application, the ion exchange membrane is subjected to a third drying, especially continued to be dried in an oven for a relatively long time, so that the organic solvent can be completely volatilized and the polymer can be fully fixed.
[0115] In some embodiments, the temperature of the third drying is 30-100°C, including but not limited to 35°C, 50°C, 60°C, 70°C, 80°C or 90°C.
[0116] In some embodiments, the third drying time is 1-48 hours, including but not limited to 5 hours, 10 hours, 20 hours, 30 hours or 40 hours.
[0117] In some embodiments, the third drying method includes at least one of air drying, vacuum drying, and constant temperature heating.
[0118] Exemplarily, forced air drying is performed in a laboratory forced air oven, vacuum drying is performed in a vacuum drying oven, and constant temperature heating is performed on a constant temperature heating table.
[0119] In some embodiments, the coating methods in the step of forming the first coating on the nanoscale pore layer and the step of forming the second coating on the sub-nanoscale pore layer both include at least one of spray coating, scraper coating, and spin coating.
[0120] As a preferred example, the coating methods in the step of forming the first coating layer on the nanoscale pore layer and the step of forming the second coating layer on the sub-nanoscale pore layer are both spray coating.
[0121] Exemplarily, a spray gun is used to uniformly spray the dispersion of the ion exchange polymer on at least a portion of the surface of the nanoscale pore layer facing away from the sub-nanoscale pore layer and on at least a portion of the surface of the nanoscale pore layer facing away from the sub-nanoscale pore layer.
[0122] In some embodiments, in the step of forming the first coating layer on the nanoscale porous layer, the surface of the nanoscale porous layer facing away from the sub-nanoscale porous layer is the upper surface of the support.
[0123] In some embodiments, in the step of forming the second coating layer on the sub-nanoscale pore layer, the surface of the sub-nanoscale pore layer facing away from the nanoscale pore layer is the upper surface of the support.
[0124] As an alternative example, Figure 1 As shown, the method for preparing the ion exchange membrane of the embodiment of the present application comprises the following steps:
[0125] S1. Preparation of ion exchange polymer dispersion: Mix the ion exchange polymer and the organic solvent according to a proportion, stir evenly, and prepare the ion exchange polymer dispersion.
[0126] S2. Spraying on the nano-support side (i.e., the surface of the nano-scale pore layer facing away from the sub-nano-scale pore layer): using a spray gun to evenly spray a quantitative ion exchange polymer dispersion on the nano-support side.
[0127] S3, solvent drying: drying the organic solvent on the surface of the membrane obtained in step S2 at a certain temperature in a forced air oven.
[0128] S4, spraying on the sub-nano support side (the surface of the sub-nanoscale pore layer facing away from the nanoscale pore layer): use a spray gun to evenly spray a quantitative ion exchange polymer dispersion on the nano support side.
[0129] S5, solvent drying: drying the organic solvent on the surface of the membrane obtained in step S4 at a certain temperature in a forced air oven.
[0130] The steps S1 to S5 are repeated until the expected loading amount of the ion exchange polymer membrane suspension is completely loaded on the support. The prepared membrane is kept in the oven for a long time to achieve complete volatilization of the organic solvent and sufficient fixation of the polymer.
[0131] Exemplarily, the amount (ie, the quantitative amount) of the ion exchange polymer dispersion sprayed in step S2 and step S4 is 0.5-5 mL.
[0132] The method for preparing the ion exchange membrane described in the present application, in addition to the beneficial effects of the ion exchange membrane described in the present application, can also bring the following beneficial effects: the process is safe, simple, low in energy consumption, and can be scaled up.
[0133] The ion exchange membrane and preparation method thereof of the embodiments of the present application provide a new idea for improving the application of electrodialysis technology in the field of extreme membrane concentration.
[0134] <Application of ion exchange membrane>
[0135] The ion exchange membrane of the embodiment of the present application, or the ion exchange membrane prepared by the preparation method of the ion exchange membrane of the embodiment of the present application, can be widely used in the field of membrane separation technology, especially in the membrane concentration process of electrodialysis technology.
[0136] <Electrodialysis Device>
[0137] The electrodialysis device of the embodiment of the present application comprises an anode, a cathode, a cation exchange membrane and an anion exchange membrane. The cation exchange membrane and / or the anion exchange membrane is the ion exchange membrane of the embodiment of the present application, or is an ion exchange membrane prepared by the preparation method of the ion exchange membrane of the embodiment of the present application.
[0138] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0139] Example 1
[0140] The preparation method of the ion exchange membrane of this embodiment uses a commercially available stacked nano-scale pore layer and a sub-nano-scale pore layer as a support (DF30 membrane of OriginWater Membrane Technology Co., Ltd.), wherein: the nano-scale pore layer is a porous structure membrane made of polysulfone, the pore size of the nano-scale pores ranges from 80-400nm, and the thickness is 35μm; the sub-nano-scale pore layer is a thin film made of polyamide, the pore size of the sub-nano-scale pores is 0.45nm, and the thickness is 20nm. The TEM image of the support is shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that the loose porous structure on the upper left side is a nanoscale pore layer, and the continuous thin layer at the lower right edge of the nanoscale pore layer is a sub-nanoscale pore layer.
[0141] like Figure 1 As shown, the preparation method comprises the following steps:
[0142] (1) Preparation of ion exchange polymer dispersion:
[0143] A 20 wt % Nafion (DuPont, D2020) solution was mixed with anhydrous ethanol at a mass ratio of 1:9, and stirred for 12 h under sealed conditions to prepare a 2 wt % cation exchange polymer dispersion.
[0144] The solvent in the 20 wt % Nafion solution is a mixed solvent of water and propanol in a mass ratio of 17:22.
[0145] (2) Spraying on the nano-support side (i.e., the surface of the nano-scale pore layer facing away from the sub-nano-scale pore layer):
[0146] Use a spray gun at 0.04 mL / min cm 2 The ion exchange polymer dispersion obtained in step (1) is uniformly sprayed on the nano support side at a speed of 100° and the spraying is continued for 1 minute to obtain a first composite membrane.
[0147] (3) Solvent drying:
[0148] The first composite membrane obtained in step (2) is placed in a forced air oven and dried at a constant temperature of 50° C. for about 10 minutes to completely volatilize the solvent of the first composite membrane obtained in step (2) (the solvent in the anhydrous ethanol and 20 wt % Nafion solution).
[0149] (4) Spraying on the sub-nanometer support side (i.e., the surface of the sub-nanometer pore layer facing away from the nano-pore layer):
[0150] The first composite film was taken out of the blast oven and sprayed with a spray gun at a rate of 0.04 mL / min cm 2 The ion exchange polymer dispersion obtained in step (1) is uniformly sprayed on the sub-nanometer support side at a speed of 10000 g / cm2 for 1 minute to obtain a second composite membrane.
[0151] (5) Solvent drying:
[0152] The second composite membrane obtained in step (4) is placed in a forced air oven and dried at a constant temperature of 50° C. for about 10 minutes to completely volatilize the surface solvent (the solvent in the anhydrous ethanol and 20 wt % perfluorosulfonic acid resin solution) of the second composite membrane obtained in step (4).
[0153] The steps (1) to (5) were cycled 16 times in total, and the final ion exchange polymer loading was about 80 mg / cm 2 The third composite membrane was kept in the oven at 50° C. for 12 h to ensure that the polymer was fully dried and stable, thereby obtaining the ion exchange membrane of this embodiment.
[0154] Figure 3 This is a transmission electron microscope (TEM) image of the ion exchange membrane prepared in Example 1. Figure 3 It can be seen that the nanoscale pores in the support are fully filled with ion exchange polymers, and the sub-nanoscale pore layer still maintains good continuity.
[0155] Example 2
[0156] This embodiment is basically the same as Embodiment 1, except that:
[0157] The preparation process of step (1) ion exchange polymer dispersion is as follows: 10wt% Fumiom (FUMA-Tech, FAA-3) solution is mixed with anhydrous ethanol in a mass ratio of 1:4, and stirred continuously for 12 hours under sealed conditions to prepare a 2%wt anion exchange polymer dispersion.
[0158] The solvent in the 10 wt % Fumiom solution is N-methylpyrrolidone.
[0159] Example 3
[0160] This embodiment is basically the same as Embodiment 1, except that:
[0161] The steps (1) to (5) were cycled once, and the final ion exchange polymer loading was 2 mg / cm 2 .
[0162] Example 4
[0163] This embodiment is basically the same as Embodiment 1, except that:
[0164] The steps (1) to (5) were cycled 40 times in total, and the final ion exchange polymer loading was 200 mg / cm 2 .
[0165] Example 5 (the material of the nanoscale pore layer is porous ceramic)
[0166] This embodiment is basically the same as Embodiment 1, except that:
[0167] The nano-scale pore layer is a porous structure membrane made of porous ceramic material (a zirconia ceramic sheet with a pore size range of 200-500nm and a thickness of 0.2μm).
[0168] Example 6
[0169] This embodiment is basically the same as Embodiment 1, except that:
[0170] The pore size of nanoscale pores ranges from 450-800 nm.
[0171] Example 7
[0172] This embodiment is basically the same as Embodiment 1, except that:
[0173] The thickness of the nanoscale pore layer is 150 μm.
[0174] Example 8
[0175] This embodiment is basically the same as Embodiment 1, except that:
[0176] The sub-nanoscale pores have a pore diameter of 0.9 nm and a thickness of 20 nm.
[0177] Example 9
[0178] This embodiment is basically the same as Embodiment 1, except that:
[0179] The thickness of the sub-nanoscale pore layer is 300 nm.
[0180] Example 10
[0181] This embodiment is basically the same as Embodiment 1, except that:
[0182] In step (1), the 20 wt % Nafion solution was replaced with a 25 wt % Aquivion solution (D98, Solvay).
[0183] The solvent in the 25 wt % Aquivion solution is a mixed solvent of water and propanol in a mass ratio of 1:1.
[0184] Comparative Example 1
[0185] The ion exchange membrane of this comparative example is a commercially available cation exchange membrane, specifically C1Snw-70 (Shandong Tianwei Membrane Technology Co., Ltd.).
[0186] Comparative Example 2
[0187] The ion exchange membrane of this comparative example is a commercially available anion exchange membrane, specifically A1Snw-70 (Shandong Tianwei Membrane Technology Co., Ltd.).
[0188] Application Example 1 (Comparison with the concentration capacity of commercial membranes)
[0189] The concentration test of the ion exchange membrane prepared by the above method in the electrodialysis technology is as follows:
[0190] Experimental group: The ion exchange membranes prepared by the methods of Example 1 and Example 2 were assembled in Figure 4 The laboratory-made electrodialysis test device shown in the figure. Among them: the ion exchange membrane prepared in Example 1 is placed in the third position 3 as the first cation exchange membrane; the ion exchange prepared in Example 2 is placed in the fourth position 4 as the first anion exchange membrane; the commercial anion exchange membrane A1Snw-70 of Comparative Example 2 and the commercial cation exchange membrane C1Snw-70 of Comparative Example 1 are assembled at position 2 and position 5 respectively. Through the above-mentioned settings, the concentrated liquid 8 and the desalinated liquid 9 are separated by a pair of ion exchange membranes prepared by the methods of Example 1 and Example 2. The effective membrane area in the device is 25cm 2 , the flow channel thickness is 5mm.
[0191] Control group: basically the same as the experimental group, except that the commercial cation exchange membrane C1Snw-70 of comparative example 1 and the commercial anion exchange membrane A1Snw-70 of comparative example 2 are respectively set at position 3 and position 4. Therefore, the concentrated liquid 8 and the desalinated liquid 9 of the control group are separated by a pair of commercial ion exchange membranes.
[0192] Before the test, 1 L 35 g / L NaCl aqueous solution, 0.015 L 35 g / L NaCl aqueous solution, and 1 L 35 g / L NaCl aqueous solution were circulated into the electrode solution 7, the concentrated solution 8, and the desalinated solution 9 at a flow rate of 5 mL / min, respectively.
[0193] In the experimental group and the control experimental group, the anode 1 at the first position is a ruthenium-iridium-coated titanium electrode connected to the positive electrode of the external power supply; the cathode 6 at the sixth position is a ruthenium-iridium-coated titanium electrode connected to the negative electrode of the external power supply. The external power supply applies 50 mA (2 mA / cm 2 ) Constant current, the experiment begins. The conductivity meter records the conductivity changes of the concentrate and desalinated liquid to obtain the concentration changes, and the recording balance continuously records the mass changes of the concentrate to obtain the water and salt migration fluxes in the membrane concentration process. Figure 5 The effluent concentration shows that the maximum concentration difference between the concentrate and fresh water in the experimental group is 94.8 g / L, which is much larger than the maximum concentration difference (35.9 g / L) in the control group (commercial membrane). The results show that the concentration performance of the ion exchange membrane prepared in the example is better than that of the commercial membrane.
[0194] Application Example 2 (Effect of Current Density)
[0195] This application example is basically the same as application example 1, except that: there is no control group, and:
[0196] The same test method as in the experimental group of Application Example 1 was used, and the operating current was set to 2 mA / cm 2 , 10mA / cm 2 , 20mA / cm 2 and 40mA / cm 2 The effect of current density on the concentration performance of the ion exchange membranes prepared by the methods of Examples 1 and 2 was investigated. Figure 6 The maximum concentration difference increases with the increase of current density. 2 The maximum concentration difference is 185g / L.
[0197] Application Example 3 (Long-term stability)
[0198] This application example is basically the same as application example 1, except that: there is no control group, and:
[0199] The same test device as in the experimental group of Application Example 1 was used. The concentrated liquid 8 and the desalinated liquid 9 were circulated with 0.015L 200g / L NaCl aqueous solution and 5L 35g / L NaCl aqueous solution at a flow rate of 5mL / min, respectively. The operating current was set to 20mA / cm 2 The operation time is 72 hours, and the operation stability of the ion exchange membranes prepared in Example 1 and Example 2 is investigated. The concentrations of the concentrate and the desalinated liquid and the quality data of the concentrate during the test are shown in FIG. Figure 7 .
[0200] During the 72-hour continuous operation, the single-stage NaCl salt difference was maintained at about 155.21 g / L (fresh water: 16.31 g / L; concentrated water: 171.52 g / L), and the salt-water selectivity did not show obvious attenuation during the 72-hour continuous operation. The mass increase rate of the concentrated liquid was basically constant, indicating that the water permeation rate of the ion exchange membrane prepared in Example 1 and Example 2 was basically stable. The long-term stability of the concentration difference and the water permeation rate confirmed that the ion exchange membranes prepared in Example 1 and Example 2 had good salt-water selectivity and stability.
[0201] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0202] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0203] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. An ion exchange membrane, characterized in that: The invention comprises a support body, wherein the support body comprises a nanoscale pore layer and a sub-nanoscale pore layer arranged in a stacked manner, wherein at least a first coating is provided on at least a portion of the surface of the nanoscale pore layer facing away from the sub-nanoscale pore layer, and at least a second coating is provided on at least a portion of the surface of the sub-nanoscale pore layer facing away from the nanoscale pores, wherein the materials of the first coating and the second coating both comprise ion exchange polymers, and the material of the first coating is embedded in at least a portion of the nanoscale pores of the nanoscale pore layer.
2. The ion exchange membrane according to claim 1, characterized in that The sub-nanoscale pores in the sub-nanoscale pore layer have a pore size range of 0.2-0.9 nm; and / or, The thickness of the sub-nanoscale pore layer is 10-500 nm; and / or, The pore size of the nanoscale pores in the nanoscale pore layer is in the range of 5-800 nm; and / or, The thickness of the nanoscale pore layer is 10-200 μm.
3. The ion exchange membrane according to claim 1 or 2, characterized in that The sub-nanoscale pore layer is a sub-nanopore film formed by a polymer, and the polymer includes at least one of polyamide, polyester, and polyphenol; and / or, The nanoscale pore layer is a porous structure membrane constructed of organic material or inorganic material; the organic material includes at least one of polysulfone, polyethylene, polyvinylidene fluoride, and polyacrylonitrile; and / or the inorganic material includes at least one of molecular sieves, porous ceramics, titanium oxide, and silicon oxide. The ion exchange polymer includes at least one of a sulfonic acid group-modified molecular chain polymer with negative charge and a quaternary ammonium group-modified molecular chain polymer with positive charge, preferably at least one of Nafion, Aquivion, Fumiom and PiperION.
4. The ion exchange membrane according to claim 1 or 2, characterized in that In the ion exchange membrane, the total loading of the ion exchange polymer is 2-200 mg / cm 2 and / or, The first coating and the second coating are made of the same material; and / or, The thickness of the first coating is 2-200 μm; and / or, The thickness of the second coating layer is 0.1-10 μm.
5. A method for preparing an ion exchange membrane according to any one of claims 1 to 4, characterized in that: The method comprises the steps of forming the first coating layer on the nanoscale pore layer and forming the second coating layer on the sub-nanoscale pore layer; The forming of the first coating on the nanoscale pore layer comprises: coating the dispersion of the ion exchange polymer on at least a portion of the surface of the nanoscale pore layer on a side away from the sub-nanoscale pore layer, and then performing a first drying; The forming of the second coating layer on the sub-nanoscale pore layer comprises: coating the dispersion of the ion exchange polymer on at least a portion of the surface of the sub-nanoscale pore layer facing away from the nanoscale pore layer, and then performing a second drying.
6. The preparation method according to claim 5, characterized in that: Firstly, forming the first coating layer on the nanoscale pore layer, and then forming the second coating layer on the sub-nanoscale pore layer; and / or, The method for preparing the ion exchange membrane further comprises: cyclically performing the step of forming the first coating on the nanoscale pore layer and the step of forming the second coating on the sub-nanoscale pore layer until the ion exchange polymer reaches a desired loading amount to obtain the ion exchange membrane; and / or, The method for preparing the ion exchange membrane further comprises: mixing the ion exchange polymer with an organic solvent to obtain a dispersion of the ion exchange polymer.
7. The preparation method according to claim 6, characterized in that: The expected loading amount is the ratio of the loading mass of the ion exchange polymer after drying to the support area, and the expected loading amount is 2-200 mg / cm 2 and / or, The organic solvent comprises at least one of ethanol, N-methylpyrrolidone and dimethylformamide; and / or, The mass fraction of the ion exchange polymer in the dispersion of the ion exchange polymer is 0.1-50%; and / or, The method for preparing the ion exchange membrane also includes: when the ion exchange polymer reaches the expected load, subjecting the ion exchange membrane to a third drying; preferably, the temperature of the third drying is 30-100°C, and / or the time of the third drying is 1-48h, and / or the method of the third drying includes at least one of forced air drying, vacuum drying, and constant temperature heating.
8. The preparation method according to claim 5, characterized in that: The coating methods in the step of forming the first coating on the nanoscale pore layer and the step of forming the second coating on the sub-nanoscale pore layer both include at least one of spray coating, scraper coating, and spin coating; and / or, In the step of forming the first coating layer on the nanoscale pore layer, the surface of the nanoscale pore layer facing away from the sub-nanoscale pore layer is the upper surface of the support; and / or, In the step of forming the second coating layer on the sub-nanoscale pore layer, the surface of the sub-nanoscale pore layer facing away from the nanoscale pore layer is the upper surface of the support; and / or, The first drying and the second drying methods both include at least one of air drying, vacuum drying, and constant temperature heating; and / or, The temperatures of the first drying and the second drying are both 30-100° C.; and / or, The time for the first drying and the second drying are both 0.1-2 hours.
9. Use of the ion exchange membrane according to any one of claims 1 to 4 or the ion exchange membrane prepared by the preparation method according to any one of claims 5 to 8 in the field of membrane separation technology.
10. An electrodialysis device comprising an anode, a cathode, a cation exchange membrane and an anion exchange membrane, characterized in that: The cation exchange membrane and / or the anion exchange membrane is an ion exchange membrane as described in any one of claims 1 to 4 or an ion exchange membrane prepared by the preparation method as described in any one of claims 5 to 8.